Mengenal Millah Ibrahim dalam Perspektif Al-Qur’an - Hamdani Anwar (LP2M Universitas PTIQ Jakarta, 2019)
This artilce elaborates the meaning of millah Ibrahim, which is, the Sh ar i’a(law) that has been revealed by the Allmighty to the Prophet Ibrahim, then, to be taught to His companions (ummah) and to be hold fast by His offsprings. the Ibrahim tawheedteaching is the meaning of millah Ibrahimthat has been mentioned in the Qur’an, so that all the samawireligions have the same basic teaching, called tawheed, however each of their prophets teach a different Shar i’a(law) between one and another. Such thing is reasonable, for each prophet is sent in different time, and the Sh ar i’ashould be adjusted according the condition of its ummah. It is no wonder wether the followers among the samawireligions conduct different religious activities one another. But, it can be confirmed that there is any previous messenger teaching which is still available for the recent time. From this, inevitability appears that in some Islamic legal system (Sh ar i’a/law) consists of previous one, which in this case is millah Ibrahim.